Muscle Architectural and Functional Adaptations Following 12-Weeks of Stretching in Adolescent Female Athletes - Panidi, Ioli; Bogdanis, Gregory C.; Terzis, Gerasimos; Donti, Anastasia; Konrad, Andreas; Gaspari, Vasiliki; Donti, Olyvia (Frontiers in Physiology, 2021)
This study examined the effects of high-volume static stretching training on gastrocnemius muscle architecture, ankle angle and jump height in 21 female adolescent volleyball players. Static stretching of the plantar flexors of one leg (STR) was performed 5 times/week for 12 weeks, in addition to volleyball training, with the contra-lateral leg used as control (CON). Total duration of stretching per session increased from 540 s (week 1) to 900 s (week 12). At baseline, week 12 and after 3 weeks of detraining, muscle architecture at the middle and the distal part of both gastrocnemius heads (medialis and lateralis) and ankle angle were examined at rest and at maximum dorsiflexion. At the same time-points gastrocnemius cross-sectional area (CSA) was also assessed, while jumping height was measured at baseline and week 12. Following intervention, ankle dorsiflexion increased in both legs with a greater increase in STR than CON (22±20% vs. 8±17%, p<0.001). Fascicle length at the middle part of gastrocnemius medialis increased only in the STR, at rest (6±7%, p=0.006) and at maximum dorsiflexion (11±7%, p<0.001). Fascicle length at maximum dorsiflexion also increased at the distal part of gastrocnemius lateralis of STR (15±13%, p<0.001). A greater increase in CSA (23±14% vs. 13±14%, p<0.001) and in one-leg jumping height (27±30% vs. 17±23%, p<0.001) was found in STR than CON. Changes in ankle angle, fascicle length and CSA were maintained following detraining. High-volume stretching training for 12 weeks results in ankle dorsiflexion, fascicle length and muscle cross sectional area increases in adolescent female volleyball players. These adaptations may partly explain improvements in jump performance.